Longitudinal study of changing psychological outcomes following the Victorian Black Saturday bushfires. (June 2018) - Bryant, Richard A; Gibbs, Lisa; Gallagher, Hugh Colin; Pattison, Phillipa; Lusher, Dean; MacDougall, Colin; Harms, Louise; Block, Karen; Sinnott, Vikki; Ireton, Greg; Richardson, John; Forbes, David
Objectives: To map the changing prevalence and predictors of psychological outcomes in affected communities 5 years following the Black Saturday bushfires in Victoria. Method: Follow-up assessment of longitudinal cohort study in high, medium and non-affected communities in Victoria, Australia. Participants included 1017 respondents (Wave 1) interviewed via telephone and web-based survey between December 2011 and January 2013, and 735 (76.1%) eligible participants were retested between July and November 2014 (Wave 2). The survey included measures of fire-related and subsequent stressful events, probable posttraumatic stress disorder, major depressive episode, alcohol use and severe distress. Results: There were reduced rates of fire-related posttraumatic stress disorder (8.7% vs 12.1%), general posttraumatic stress disorder (14.7% vs 18.2%), major depressive episode (9.0% vs 10.9%) and serious mental illness (5.4% vs 7.8%). Rates of resilience increased over time (81.8% vs 77.1%), and problem alcohol use remained high across Wave 1 (22.1%) and Wave 2 (21.4%). The most robust predictor of later development of fire-related posttraumatic stress disorder (odds ratio: 2.11; 95% confidence interval: [1.22, 3.65]), general posttraumatic stress disorder (odds ratio: 3.15; 95% confidence interval: [1.98, 5.02]), major depressive episode (odds ratio: 2.86; 95% confidence interval: [1.74, 4.70]), serious mental illness (odds ratio: 2.67; 95% confidence interval: [0.57, 1.72]) or diminished resilience (odds ratio: 2.01; 95% confidence interval: [1.32, 3.05]) was extent of recent life stressors. Conclusion: Although rates of mental health problems diminished over time, they remained higher than national levels. Findings suggest that policy-makers need to recognize that the mental health consequences of disasters can persist for many years after the event and need to allocate resources towards those who are most at risk as a result of substantive losses and ongoing life stressors.